IMPLEMENTASI PROGRAM PEMBELAJARAN TAHFIDZ AL-QUR’AN DI PONDOK PESANTREN TAHFIDZUL QUR’AN SYECH AHMAD CHATIB AL-MINANGKABAWI - Saipul Anwar; Iswantir M (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2023)
Tahfidzul Qur'an Syech Ahmad Chatib al-Minangkabawi Islamic Boarding School, found proud academic achievements, especially in the MTQ, MHQ branches at the District, Regency, Provincial and National levels. This research is qualitative field research. Data was obtained through observation, interviews and documentation studies. Informants were selected using the "Purposive Sampling" technique. The results of this research show that the tahfidz learning program is targeted at 10 juz for Mts/Junior High School level and 20 Juz for Aliyah/Senior High School level. The implementation schedule for the tahfidz learning program is two times, first, Maghrib between after maghrib prayer until before evening prayer (18.40-19.50) , After Isha' (20.15-10.00) and Fajr from (04.30-06.50), there is added new memorization, muraja'ah memorization. Second, in the morning formal school hours (KBM) at the local area for deepening the tahsinul Qur'an material, talaqqi method, formative evaluation and summative evaluation, obstacles found in implementing tahfidz Al-Qur'an learning during Covid 19.